2014
DOI: 10.1007/s11655-014-2024-y
|View full text |Cite
|
Sign up to set email alerts
|

Review of the regulations for clinical research in herbal medicines in USA

Abstract: In 2012, USA Food and Drug Administration (FDA) approved 39 new drugs, however, there are only two botanical drugs (one topical and one oral) approved by FDA since the publication of the FDA's industry guidelines for the botanical drug product in June 2004. The approval shows the Western guideline can be used for herbal medicines, authors investigate current regulation on herbal medicine clinical research, identify challenges conducting clinical trials, and seek to produce some guidance for potential investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…Indeed, a number of clinical trials have been conducted [ 20 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] for medicinal herbs and plant extracts, which surely has and will in the future further increase the credibility of plant-based drugs. However, among the 39 new drugs approved by the US Food and Drug Administration (FDA), only two were described as botanical drugs [ 62 ]. In this context, the first FDA approved plant-based drug, Veregen, a green tea leaf extract used as a topical cream for perianal and genital condyloma, has been critically evaluated for the establishment of a Checklist for New Drug Application of Herbal Medicines for future development of clinical trials on herbal medicines [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of clinical trials have been conducted [ 20 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] for medicinal herbs and plant extracts, which surely has and will in the future further increase the credibility of plant-based drugs. However, among the 39 new drugs approved by the US Food and Drug Administration (FDA), only two were described as botanical drugs [ 62 ]. In this context, the first FDA approved plant-based drug, Veregen, a green tea leaf extract used as a topical cream for perianal and genital condyloma, has been critically evaluated for the establishment of a Checklist for New Drug Application of Herbal Medicines for future development of clinical trials on herbal medicines [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALI is a life-threatening disease for which no effective treatments are available. Botanical drugs are considered to be an important resource for drug development, and they require stringent testing for efficacy, safety and quality 9 . Because of the ability of IKWE to inhibit HNE activity, the protective effects of I. kaushue against ALI were investigated, both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Botanical products and TCM are recognized as important sources of novel drugs 8 9 . In an attempt to identify NE inhibitors, 22 TCM extracts were prepared and their inhibitory effects on human neutrophil elastase (HNE) activity evaluated.…”
mentioning
confidence: 99%
“…Clinical studies demonstrated that many medicinal plants can efficiently regulate the human immune system and inflammation [4,5]. In 2002, e Food and Drug Administration (FDA) approved 39 new drugs including two botanical drugs (oral and topical) [6]. e chemical compositions of traditional Chinese medicines (TCMs) are complex; the quality of TCM cannot be comprehensively and effectively controlled only by one or several [7][8][9].…”
Section: Introductionmentioning
confidence: 99%